1992
DOI: 10.1103/physrevlett.69.680
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence ofTcand charge transfer inYBa2

Abstract: The superconducting critical temperature T c of YBa2Cu30 x single crystals (6.35^x^7) has been measured resistively as a function of pressure P (0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(63 citation statements)
references
References 18 publications
5
58
0
Order By: Relevance
“…Therefore, it is natural to expect a nearly zero oxygen isotope effect in the optimally doped YBa 2 Cu 3 O 7Ϫ␦ for a BCS-type electron-phonon interaction pairing. It is worth noting that the doping dependence of ␣ in YBa 2 Cu 3 O 7Ϫ␦ resembles that of dlnT c /dP (36,37), signaling a nice correlation between the isotope and pressure effects.…”
Section: [3]mentioning
confidence: 99%
“…Therefore, it is natural to expect a nearly zero oxygen isotope effect in the optimally doped YBa 2 Cu 3 O 7Ϫ␦ for a BCS-type electron-phonon interaction pairing. It is worth noting that the doping dependence of ␣ in YBa 2 Cu 3 O 7Ϫ␦ resembles that of dlnT c /dP (36,37), signaling a nice correlation between the isotope and pressure effects.…”
Section: [3]mentioning
confidence: 99%
“…Murayama et al [21] showed from Hall coefficient measurements on Y124, Bi2212 and Tl221 that T c follows the T c (n h ) parabola via pressure induced doping, whereas for doped La214 a complete shift of the parabola to higher T c values and no pressure induced doping effect was found [44]. Almasan et al [35] and Iye [45] extended the simple charge transfer model assuming that the effect of pressure on T c consists of a change of the carrier density and an additional shift of the complete T c parabola to higher T c values expressed by dT c,max /dp. The influence of pressure on T c,max can easily be determined when T c,max is known at ambient pressure because in the maximum of the parabola the T c variation due to a pressure induced change of the hole concentration is zero.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of experiments have been performed to determine dT c /dp of doped Y123 compounds [19,21,35,37,43,47,49,58,[64][65][66][67][68][69][70][71]. In the beginning of these investigations the results from different groups showed large scatter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations